Combined hepatectomy and microwave ablation for multifocal hepatocellular carcinoma: Long-term outcomes and prognostic factors - Tomoki Ryu; Yuko Takami; Yoshiyuki Wada; Shin Sasaki; Hajime Imamura; Hiroki Ureshino; Hideki Saitsu (Asian Journal of Surgery, 2021)
Background: It remains to be clarified whether combined hepatectomy and microwave ablation for multifocal hepatocellular carcinoma (HCC) is feasible. This aim of this study was to examine the perioperative and oncological outcomes after combined hepatectomy and microwave ablation for multifocal HCC. Methods: This retrospective study included 81 patients who underwent combined hepatectomy and microwave ablation for multifocal HCC in our institute between June 1998 and December 2017. We analyzed overall survival (OS) and recurrence-free survival (RFS), and evaluated factors related to prognosis. Results: Median follow-up time was 45.6 months for the entire cohort. OS rates were 1-year: 96%, 3-year: 72%, and 5-year: 54%; RFS rates were 1-year: 77%, 3-year: 37%, and 5-year: 22%. The major complication rate (Clavien–Dindo classification IIIa or above) after surgery was 10%, with one patient of in-hospital mortality. Multivariate analysis revealed that des-γ-carboxy prothrombin level >200 mAU/mL and >5 tumors were independent risk factors for OS, and des-γ-carboxy prothrombin level >200 mAU/mL, > 5 tumors, and maximum tumor size >5 cm were independent risk factors for RFS. Conclusions: Our results indicate that combined hepatectomy and microwave ablation is safe and feasible for selected patients with multifocal HCC.